2014
DOI: 10.5628/rpcd.14.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Desafios nutricionais de bailarinos profissionais

Abstract: Desafios nutricionais de bailarinos profissionais PALAVRAS CHAVE:Dança. Nutrição. Controlo ponderal. RESUMOA dança caracteriza-se pela acentuada solicitação dos vários sistemas orgânicos na procura e manutenção de corpos funcionalmente aptos e esteticamente belos. A dança, embora seja essencialmente arte, ao procurar a máxima expressão visual e artística determina um grau de solicitação neuro-motora que obriga o corpo a elevadas exigências fisiológicas e biomecânicas. Quanto mais pesado o corpo do bailarino/a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…However, the search for excessive thinness can lead to pathological situations such as the development of eating disorders. 1,16,32 Hence the present study found an association between dissatisfaction with the percep-tion of being overweight and eating disorders, with a 3% greater chance for those professional dancers showing higher EAT scores and a 28% greater chance for those presenting higher scores on the BITE symptom scale to develop these disorders. The current literature confirms these tendencies, indicating that dancers as a population are exceptionally prone to dissatisfaction due to the perception of being overweight 17,30,31,33 and consequently to eating disorder symptoms, 3,10,16,32,34 all of which are 28% more prevalant in females than males.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, the search for excessive thinness can lead to pathological situations such as the development of eating disorders. 1,16,32 Hence the present study found an association between dissatisfaction with the percep-tion of being overweight and eating disorders, with a 3% greater chance for those professional dancers showing higher EAT scores and a 28% greater chance for those presenting higher scores on the BITE symptom scale to develop these disorders. The current literature confirms these tendencies, indicating that dancers as a population are exceptionally prone to dissatisfaction due to the perception of being overweight 17,30,31,33 and consequently to eating disorder symptoms, 3,10,16,32,34 all of which are 28% more prevalant in females than males.…”
Section: Discussionsupporting
confidence: 50%
“…D edication to a professional career in dance requires a high level of functional aptitude and an aesthetically beautiful body. 1,2…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A dança é uma expressão corporal e tem exigências estéticas que incentivam os seus praticantes ao controle nutricional excessivo para manter uma adequação da silhueta corporal exigida. Cada dançarino desempenha sua habilidade dentro do limite de competência fisiológica e biomecânica, destacando-se aqueles que apresentam a melhor capacidade física (LANCHA JÚNIOR, 2011;AMORIM, 2014).…”
Section: Introductionunclassified